(3JjSjQ GdhUhd Edi LGeY GdCUhds - (3YHO GdQMef Hf Ydj Hf eMeO Hf YeQ GdOjHY GdTjHGfis; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3CMeO Hf bGSe Hf Ydi Hf bGSe GdYRhi GdTjHGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi jSQ GdhUhd Edi LGeY GdCUhd , ef MOjK GdQShd , hSgd fMh KdK MLeg ENJUGQg eY MSf GdEjQGO s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3cdeJGf NajaJGf Ydi GddSGf KbjdJGf ai GdejRGf MHjHJGf Edi GdQMef SHMGf Gddg hHMeOg SHMGf Gddg GdYXje , BNQ Gd LRA GdKGfi hHJeGeI Je LejY GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdLRA GdChd ef fSNI CNQi cJHJ SfI (B988s
(3cJHJ HQSe TjN GdESdGe LeGd GdOjf eMeO Hf CSMes
(3GdfSNI ebGHdI Ydi fSNI ebGHdI fSNI GdeUfais
(3cJHJ GdYfhGfGJ HGdMeQI s
(3HChdgG hBNQgG SeGYGJ hJedcGJ eJbOeI s
(3GdfSNI HgG MhGT s
Keywords: (3GdMOjK h GdeUWdMs